2021
DOI: 10.22336/rjo.2021.69
|View full text |Cite
|
Sign up to set email alerts
|

Rhino-orbital mucormycosis: Our experiences with clinical features and management in a tertiary care center

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In our reviewed studies, the specific indications for retrobulbar injection of the drug were visual loss, signs of orbital apex involvement, and progression of the disease despite appropriate systemic medical and surgical treatments. 25 , 28 31 , 33 , 34 Similar indications were elucidated by Hirabayashi et al 19 In addition, we found that this route of the drug administration should be considered in earlier stages, especially in cases that are not good candidates for extensive surgical interventions (i.e., pediatrics and admitted patients to an intensive care unit, ICU). 29 , 31 In the COVID-19 era, many cases are admitted to the ICU and, therefore, are not candidates with favorable outcomes following surgical interventions (including paranasal sinuses and orbital debridements).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In our reviewed studies, the specific indications for retrobulbar injection of the drug were visual loss, signs of orbital apex involvement, and progression of the disease despite appropriate systemic medical and surgical treatments. 25 , 28 31 , 33 , 34 Similar indications were elucidated by Hirabayashi et al 19 In addition, we found that this route of the drug administration should be considered in earlier stages, especially in cases that are not good candidates for extensive surgical interventions (i.e., pediatrics and admitted patients to an intensive care unit, ICU). 29 , 31 In the COVID-19 era, many cases are admitted to the ICU and, therefore, are not candidates with favorable outcomes following surgical interventions (including paranasal sinuses and orbital debridements).…”
Section: Discussionsupporting
confidence: 76%
“…In addition, the injection may reduce the load of orbital disease and thus postpone future surgeries. 25 , 28 31 , 33 , 34 The outcomes of retrobulbar injections (except for globe salvage) were a preserved or enhanced ocular state through a reduction in ophthalmic signs including visual impairment, pain, swelling, ptosis, proptosis, and extraocular motility restriction. 25 , 26 , 33 – 35 Occurrence of side effects was rare and, in some, transient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scant literature is available including case reports, small data-based case series, and reviews describing an association between COVID-19 and ROCM [ Table 3 ]. [ 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 88 89 90 91 92 93 94 95 96 97 98 ] However, the swiftness and ferocity with which this pandemic has engulfed the world and the unprecedented investment of healthcare professionals and resources has made it necessary to evaluate any level of evidence available in the literature not only to guide management strategy but also to plan current and future research. With varied clinical forms of mucormycosis, pulmonary mucormycosis was the predominant clinical form (87.5%) observed, while ROCM was the most common presentation (28.6%) that was noted in developing countries like India.…”
Section: Rocm and Covid-19 Disease: Perspectives And Changing Trendsmentioning
confidence: 99%